Cord blood nesfatin-1 and apelin-36 levels in gestational diabetes mellitus - Aslan, Mehmet; Celik, Onder; Celik, Nilufer; Turkcuoglu, Ilgin; Yilmaz, Ercan; Karaer, Abdullah; Aydin, Suleyman (Springer, 2012)
To assess maternal serum and cord blood apelin-36 and nesfatin-1 concentrations in pregnant women with and without gestational diabetes mellitus (GDM). Thirty pregnant women with GDM and 30 gestational age matched healthy pregnant subjects participated to the study. Maternal serum and cord blood nesfatin-1 and apelin-36 levels were measured with ELISA, at the time of birth. The relationships between maternal serum and cord blood nesfatin-1 and apelin-36 levels, anthropometric and metabolic parameters were also assessed. Maternal serum apelin-36 levels were found higher (13.5 +/- A 8.3 vs. 9.6 +/- A 5.9 ng/ml, P = 0.001) and nesfatin-1 levels were found lower (5.5 +/- A 8.1 vs. 8.1 +/- A 23.9 ng/ml, P = 0.001) in patients with GDM compared with control pregnant women. However, the cord blood apelin-36 levels (8.8 +/- A 4.3 and 8.2 +/- A 1.9 ng/ml, P = 0.618) and nesfatin-1 levels (5.4 +/- A 4.0 and 6.2 +/- A 10.3 ng/ml, P = 0.688) were similar in the GDM and control groups, respectively. Maternal serum apelin-36 and nesfatin-1 levels correlated positively with their respective cord blood levels. Maternal serum and cord blood apelin-36 levels correlated negatively with the gestational age and birth weight. Similarly maternal serum and cord blood nesfatin-1 levels correlated negatively with the gestational age, but there was no correlation with the birth weight. We did not find a correlation between maternal serum apelin-36 and nesfatin-1 levels, maternal age, BMI, fasting glucose, fasting insulin, and HOMA-IR. Also cord blood apelin-36 and nesfatin-1 levels did not correlate with the maternal age, BMI, HOMA-IR, cord blood glucose, and cord blood insulin levels. Our results indicate that apelin-36 concentrations increase and nesfatin-1 concentrations decrease in maternal serum of women with GDM.
Keywords: Gestational diabetes mellitus; Apelin-36; Nesfatin-1; Insulin